On q-steepest descent method for unconstrained multiobjective optimization problems - Keung Lai, Kin; Kant Mishra, Shashi; Panda, Geetanjali; Abu Talhamainuddin Ansary, Md; Ram, Bhagwat (AIMS mathematics, 2020)
The q-gradient is the generalization of the gradient based on the q-derivative. The q-version of the steepest descent method for unconstrained multiobjective optimization problems is constructed and recovered to the classical one as q equals 1. In this method, the search process moves step by step from global at the beginning to particularly neighborhood at last. This method does not depend upon a starting point. The proposed algorithm for finding critical points is verified in the numerical examples.